2015
DOI: 10.1155/2015/204367
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Profiling Response to Acupuncture Therapy in Spontaneously Hypertensive Rats

Abstract: MicroRNAs (miRNAs) are a group of endogenous noncoding RNAs that play important roles in many biological processes. This study aimed to check if miRNAs were involved in the response to acupuncture in rats. Microarray analysis was performed to compare the miRNA expression profiles of medulla in spontaneously hypertensive rats (SHRs) treated with or without acupuncture. Our microarray analysis identified 222 differentially expressed miRNAs in the medulla of SHRs treated with acupuncture at taichong acupoint. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 57 publications
4
17
0
Order By: Relevance
“…These miRNA have been shown to be regulated by acupuncture treatment in the brain of SHR. 28 The present data showed that adenosine stimulation significantly downregulated miR-339, miR-145 and miR-451 expression in NGF-induced PC12 cells ( Fig. 1; *P < 0.05; ***P < 0.001).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…These miRNA have been shown to be regulated by acupuncture treatment in the brain of SHR. 28 The present data showed that adenosine stimulation significantly downregulated miR-339, miR-145 and miR-451 expression in NGF-induced PC12 cells ( Fig. 1; *P < 0.05; ***P < 0.001).…”
Section: Resultssupporting
confidence: 56%
“…To test whether adenosine stimulation could mimic the effect of acupuncture on miRNA profiles, we measured three miRNA (including miR‐339, miR‐145, and miR‐451) expression level in NGF‐induced PC12 cells. These miRNA have been shown to be regulated by acupuncture treatment in the brain of SHR . The present data showed that adenosine stimulation significantly downregulated miR‐339, miR‐145 and miR‐451 expression in NGF‐induced PC12 cells (Fig.…”
Section: Resultssupporting
confidence: 55%
“…Among them, miRNA microarray technology is a specific and efficient method to generate miRNA expression profiles. This approach has been applied to study the functional linkages between miRNAs and physiological/pathological processes . In this study, a microarray that included 5214 mature human miRNAs on the array chip was employed to analyse miRNA expression systematically in the LPS‐treated PDLCs.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of enkephalin expression was correlated with decreased brain infarction and edema ratios [15]. Acupuncture at LR3 could upregulate the miR-339, miR-223, and miR-145 microRNAs (miRNA) in the medulla [16]. miR-339 could be a pro-survival miRNA with neuroprotective effects in ischemic stroke models [17,18].…”
Section: The Potential Of Acupuncture For Secondary Prevention Of Strmentioning
confidence: 99%